2012
DOI: 10.1186/1471-2393-12-99
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experiences of factors that facilitate or inhibit gestational diabetes self-management

Abstract: BackgroundGestational diabetes rates have increased dramatically in the past two decades and this pattern of increase appears to relate primarily to the obesity epidemic, older maternal age and migration from world areas of high GDM risk. Women from disadvantaged and migrant backgrounds are most at risk of developing and of mismanaging this condition. The aim of the study was to explore the factors that facilitated or inhibited gestational diabetes self-management among women in a socially deprived area.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
171
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(184 citation statements)
references
References 45 publications
6
171
1
6
Order By: Relevance
“…On the one hand, women felt that the management of GDM added to their multiple competing responsibilities and, for some, it created financial constraints and conflicted somewhat with their cultural food practices. Our findings complement those of another recent qualitative study that identified time pressures, physical and social constraints, and limited comprehension of advice as barriers to GDM management (15).…”
Section: Discussionsupporting
confidence: 91%
“…On the one hand, women felt that the management of GDM added to their multiple competing responsibilities and, for some, it created financial constraints and conflicted somewhat with their cultural food practices. Our findings complement those of another recent qualitative study that identified time pressures, physical and social constraints, and limited comprehension of advice as barriers to GDM management (15).…”
Section: Discussionsupporting
confidence: 91%
“…Myths like “exercise harms the baby” and “pregnant mothers must consume food for two” cause negative strongholds in pregnant women, preventing them from following the instructions of their health-care professionals to exercise and adhere to a certain diet. Some patients are even reluctant to ask questions, suggesting poor interaction with the health-care providers leading to misconceptions (48, 49). Hence, many women remain sedentary during pregnancy because of these perceived barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, many women remain sedentary during pregnancy because of these perceived barriers. Many women crave certain food items during pregnancy, and the temptation for food that is not necessarily nutritious, especially carbohydrates, is a major obstacle to adherence (48, 49). Although studies suggest that exercise is good in pregnant women, in reality, compliance to diet, exercise, and medications is a major challenge to care in GDM patients, given one’s cultural habits.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple regression analysis found that current grade level In both the adolescent and adult health literacy literature, socioeconomic status (SES) has been identified as a having a significant association with health literacy. Women with lower SES had more difficulty following gestational diabetes self-management requirements as shown in a qualitative study utilizing focus groups and individual interviews (Carolan et al, 2012). SES was also a predictor of diabetes knowledge in a sample of 349 adolescents (mean age=13 years) with type 1 diabetes (Powell et al, 2013).…”
Section: Annual Household Incomementioning
confidence: 99%
“…Furthermore, women with lower SES have more difficulty following gestational diabetes selfmanagement requirements as shown in a qualitative study utilizing focus groups and individual interviews (Carolan, Gill, & Steele, 2012). In addition, lower SES is associated with lower health literacy amongst cancer patients (both urban and rural); and, low SES is a strong predictor of limited health literacy in patients on maintenance hemodialysis (Green et al, 2011;Halverson et al, 2013).…”
Section: Annual Household Incomementioning
confidence: 99%